La comunidad de suerte, las cláusulas de control y cooperación de reclamos y la cut through clause. Desdibujando las fronteras contractuales entre el seguro y el reaseguro (2020)
The close relationship between insurance and reinsurance contracts, as well as its evolution over the years, has caused the existing boundaries between one contract and the other to appear significantly blurred. The implementation of reinsurance clauses such as cut through and claims control and cooperation clauses, impact fundamental principles of the reinsurance contract, such as the commonly known as follow the fortunes, ultimately attacking the basic principle of utmost good faith. As a conclusion, it is evident that the appearance of these clauses is mainly due to the loss of confidence between the reinsurer and the reinsured.